Balancing Public Health and Human Rights: A Comparative Analysis of Sri Lanka and India in the Context of Global Health Crises - Nethmini, M.A.S. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Public health and human rights are not inherently conflicting concepts, particularly because the right to health is itself recognized as a fundamental human right. However, especially during global health crises, public health measures adopted by states can considerably restrict individual human rights. Those measures can cause contradictions between collective rights on public health and individual human rights. Consequently, an inherent tension emerges, requiring states to balance public health imperatives with their obligation to respect, protect, and fulfil fundamental individual human rights. Existing literature on this tension reveals that during the global health crises, many of the sovereign states failed to adopt the balancing criteria—primarily legality, necessity, proportionality, and non-discrimination—that have already been established by international instruments such as ICCPR, ICSER, Siracusa principles, and IHRs. However, there is a notable gap in the existing literature regarding the appropriate balancing approach Sri Lanka should adopt in future public health crises. This research addresses the gap by using a doctrinal research methodology to reveal a disconnect between Sri Lanka’s current legal framework and international balancing standards. In contrast, it reveals that as a multicultural jurisdiction, India’s legal system and judiciary have taken a constructive stance toward international balancing standards. Based on that background and acknowledging that the COVID-19 pandemic is unlikely to be the last global health emergency Sri Lanka will face, this research suggests that ensuring an appropriate balance between public health measures and fundamental rights requires Sri Lanka’s constitutional, legislative, and judicial frameworks to more fully integrate internationally recognized balancing standards.
Keywords: Public health; Human rights; Balancing standards; Sri Lanka; India